2009
DOI: 10.1080/01443410802654909
|View full text |Cite
|
Sign up to set email alerts
|

Chinese elementary school teachers’ perceptions of students’ classroom behaviour problems

Abstract: This study examined teachers' perceptions of classroom behaviour problems in five provinces of the People's Republic of China. Researchers surveyed 527 Chinese teachers from 27 elementary schools. Consistent with previous studies in China, teachers perceived non-attention to be the most frequent and troublesome behaviour problem. Teachers' perceptions of which behaviour problems were most difficult to tolerate and most negative in their effects on student development were also investigated. Approximately 45% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
1
34
0
3
Order By: Relevance
“…Teachers usually reported that these disturbing behaviors in the classroom are intolerable [2] and stress-provoking [3], and they had to spend a great deal of time and energy to manage the classroom [4, 5]. Obviously, student misbehaviors retard the smoothness and effectiveness of teaching and also impede the learning of the student and his/her classmates.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers usually reported that these disturbing behaviors in the classroom are intolerable [2] and stress-provoking [3], and they had to spend a great deal of time and energy to manage the classroom [4, 5]. Obviously, student misbehaviors retard the smoothness and effectiveness of teaching and also impede the learning of the student and his/her classmates.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they have low acceptance from their teachers (Jin et al, 2010), and behaviors such as inattention, talking out of the turn, and disrupting others are seen to have negative influences on classroom discipline (Ding, Li, Li, & Kulm, 2008;Shen et al, 2009). These perspectives are associated with a cultural belief that Chinese students are expected to be disciplined autonomously and work hard in school (Xie & Wang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Intervention in the classroom is therefore necessary in order to reduce and eliminate disruptive classroom behavior and the associated effects it has on teachers and students. Disruptive behaviors are often initially minor in nature, therefore interventions based on the principles of reinforcement and punishment have been found to be appropriate and effective, as a teacher can encourage a student to spend more time engaging in academic activities and less time behaving inappropriately (Little et al, 2002;Merrett & Tang, 1994;Wilks, 1996in Shen et al, 2009). Furthermore, Sun"s (2015) study in Hong Kong reveals that there are eight strategies that can be used to manage students" behavior in classroom activity in which seven of those are more effective: rules-setting, hinting, directive statements, punishment, after class talk, relationship building, and instructional engagement.…”
Section: Introductionmentioning
confidence: 99%